Overview of Virulence Factor of Staphylococcus sp. - Saade Abdalkareem Jasim; Omar Dheyauldeen Salahdin; Eman Naji Saleh (International Journal of Toxins and Toxics, 2024)
Staphylococcus is a highly virulent genus of bacteria that can cause a range of infections in humans and animals. The production of toxins, enzymes, and biofilms contributes to its ability to establish infections and evade host defenses. Understanding the characteristics and virulence factors of Staphylococcus is crucial for the development of effective prevention strategies and treatment options. Staphylococcus aureus is a significant etiological agent of nosocomial infections on a global scale, with particular emphasis on the prevalence of methicillin-resistant S. aureus. There is a higher risk of contracting this particular bacteria in people who take immunosuppressive drugs and broad-spectrum antibiotics. Staphylococcus aureus infections are hard to treat because there is a lot of variation within the population, including phenotypic flipping, intra-strain diversity, hypermutability, and, most importantly, the presence of small colony variations. It is very important to stress that the host's immune system is not strong enough to fight off persistent infections caused by S. aureus. This usually leads to the development of chronic infections that can become life-threatening. Throughout this chapter, our attention will be directed towards the primary facets of S. aureus pathogenicity.
Keywords: Biofilm formation; S. epidermis; Staphylococci; Staphylococcus aureus; Virulence factor